The role of large volume re-irradiation with Bevacizumab in chemorefractory high grade glioma. (May 2020) - Chan, Joseph; Jayamanne, Dasantha; Wheeler, Helen; Khasraw, Mustafa; Wong, Matthew; Kastelan, Marina; Guo, Lesley; Back, Michael
Highlights: Large volume reRT is a viable treatment for refractory recurrent high-grade glioma. Bevacizumab facilitates large volume reRT by reducing the risk of CNS radionecrosis. Patient selection for reRT needs more work but should be guided by performance status. Abstract: Background and purpose: Current practice in re-irradiation (reRT) of previously treated high-grade gliomas (HGG) has generally been limited to small volume reRT with stereotactic procedures. Less evidence exists for large volume reRT involving treatment volumes equivalent to that used at initial diagnosis. The primary aim of this study was to investigate the outcome of large volume reRT delivered in combination with Bevacizumab (BEV) in patients with recurrent chemorefractory HGG. Methods and materials: Patients with HGG managed with reRT were entered prospectively into a database. Clinicopathological features were recorded including timing of reRT, use of BEV and Dosimetric data. Median survival following reRT was the primary endpoint and association with clinicopathological factors was assessed with cox regression models. Results: Sixty seven patients in total were managed with reRT, 51 patients had glioblastoma and 16 had anaplastic glioma. The median PTV was 145.3 cm 3 . Median OS post reRT was 7.8 months (95% CI 6.3–9.2 months) in the total cohort and 7.5 months (95% CI: 6.6–8.3 months) for GBM patients. In multivariate analysis of the whole cohort, IDH1 mutation status (p = 0.041) and ECOG status prior to reRT (<0.001) were significantly associated with OS. In terms of safety and toxicity, the majority of patients (66.5%) were ECOG 0–2 three months after treatment. In total, four episodes of suspected radiation necrosis occurred, all in patients treated without upfront BEV. Conclusion: Large volume reRT with bevacizumab is a feasible late salvage option in patients with recurrent HGG and offers meaningful prolongation of survival with low toxicity.